The Analysis of Problems Causing the Inhibitors of Deaf’s Work in the Company - Prima Dea Pangestu; Imas Diana Aprilia (Department of Special Education, 2018)
The purpose of this study is to find out the description of problems causing the inhibitors of deaf’s work. This research uses the qualitative approach with descriptive method. The technique of collecting data in this research is through interview, observation and documentation study. Data analysis techniques used are through data reduction, data presentation or display data and conclusion (conclusion) and verification. From the results of the study, researcher found that there are problems for deaf in work, especially in the company due to some things that have not matured, such as the competence of the deaf, adaptation of corporate environments that are still difficult for the deaf, the inability of the company to provide services for deaf employees, and mental preparation for the deaf that is still not done in school. The conclusion of this study is, there are still many problems causing the inhibitors of deaf’s work in the company.